Mild Pd-Catalyzed Aminocarbonylation of (Hetero)Aryl Bromides with a Palladacycle Precatalyst - Friis, Stig D. (American Chemical Society, 2014)
[Image: see text] A palladacyclic precatalyst is employed to cleanly generate a highly active XantPhos-ligated Pd-catalyst. Its use in low temperature aminocarbonylations of (hetero)aryl bromides provides access to a range of challenging products in good to excellent yields with low catalyst loading and only a slight excess of CO. Some products are unattainable by traditional carbonylative coupling.